Cloud based Energy Management System Compatible with the Industry 4.0 Requirements. Issue 10 (2019) - Javied, T.; Huprich, S.; Franke, J.
Abstract: As a result of climate change and continuously rising energy costs, energy as a resource is becoming increasingly important for companies in German industry. The standards of modern companies are increasingly being enhanced by values such as energy efficiency and energy awareness in order to achieve a competitive advantage through the skillful use of resources. Energy audits and energy management systems should lead to a sustainable use of energy. This development is additionally driven by current legal requirements of energy policy which leads to the development of a new area in the market involving the sale of energy management systems and energy services in general. However, only a few system solutions fulfil all core aspects of meaningful energy management according to DIN EN ISO 50001. This paper describes a platform-independent, cloud-based web application that implements energy management in a standardized and user-friendly manner. As part of an overall solution, the multiuser system supports role-based planning, implementation, logging and archiving of the necessary work steps that emerge from the implementation of the standard. Modern communication technologies and transmission protocols enable the flexible connection of different manufacturing systems, so that energy management can fully be integrated into an industry 4.0 production environment.